Community-based participatory research to improve life quality and clinical outcomes of patients with breast cancer (DianaWeb in Umbria pilot study). Issue 6 (1st June 2016) - Villarini, Milena; Lanari, Chiara; Nucci, Daniele; Gianfredi, Vincenza; Marzulli, Tiziana; Berrino, Franco; Borgo, Alessandra; Bruno, Eleonora; Gargano, Giuliana; Moretti, Massimo; Villarini, Anna
Abstract : Introduction: Breast cancer (BC) is the most frequent cancer in Europe and the International Agency for Research on Cancer (IARC) has estimated over 460 000 incident cases per year. Survival among patients with BC has increased in the past decades and EUROCARE-5 has estimated a 5-year relative survival rate of 82% for patients diagnosed in 2000–2007. There is growing evidence that lifestyle (such as a diet based on Mediterranean principles associated with moderate physical activity) may influence prognosis of BC; however, this information is not currently available to patients and is not considered in oncology protocols. Only a few epidemiological studies have investigated the role of diet in BC recurrence and metastasis. Methods and analysis: DianaWeb is a community-based participatory research dedicated to patients with BC and represents a collaborative effort between participants and research institutions to determine if specified changes in lifestyle would result in improved outcomes in terms of quality of life or survival. The aim of the study is to recruit a large number of participants, to monitor their lifestyle and health status over time, to provide them tips to encourage sustainable lifestyle changes, to analyse clinical outcomes as a function of baseline risk factors and subsequent changes, and to share with patients methodologies and results. DianaWeb uses a specific interactive website (http://www.dianaweb.org/ ) and, with very few exceptions, all communications will be made through the web. In this paper we describe the pilot study, namely DianaWeb in Umbria. Ethics and dissemination: DianaWeb does not interfere with prescribed oncological treatments; rather, it recommends that participants should follow the received prescriptions. The results will be used to plan guidelines for nutrition and physical activity for patients with BC. The pilot study was approved by the ethics committee of the University of Perugia (reference number 2015-002), and is supported by Fondazione Cassa di Risparmio di Perugia (2013.0185 021).